Identification of Brugada Syndrome as a Quality Control Test for EMF Danger for Affected Individuals with and without Implanted Devices or Unaware of their Condition - Mazzotta, Mauro; Fernandez, Manuel; Mazzotta, Alessandro Dario; Cazzato, Rocco Giuseppe (British Journal of Healthcare and Medical Research, 2026)
We report three cases of workers with Brugada syndrome (BrS) who were fitted with an active implantable medical device (AIMD) with a defibrillator effect. In these individuals, abnormalities in sodium ion channels are the cause of acute ventricular fibrillation attacks. While the fundamental role of ICD therapy in preventing fatal arrhythmias in Brugada syndrome is obvious, device-related complications cannot be ruled out, especially in younger, working-age patients, even in cases where thoracoscopic epicardial ablation was performed in addition to the ICD with a positive outcome. However, while it is obvious in these individuals, limiting or excluding excess exposure to electromagnetic field (EMF) sources or other incompatibilities with the routine performance of certain tasks is necessary, based on necessary precautions. However, it appears difficult to diagnose Brugada syndrome or other channelopathies in subjects without device use and with an unresolved medical history, or to rule out the effect of exposure to (EMF) in those with unrecognized Brugada syndrome. The goal of this study is to clarify which specific measures could be adopted, whether they are sufficient in the most severe conditions, and whether precautionary procedures allow for continued work. Finally, it is also important to clarify a larger clinical study in the preventive phases.